Indicators of successful submissions to the Law and Social Science Program of the National Science Foundation. - Hosch, Harmon M.; Oliveri, Matthew W. (Law & Society Review, 1998)
Part of a special section on sociolegal scholarship. A study was conducted to examine the overall success of 1,428 proposals submitted to the National Science Foundation's Law and Social Science Program between 1986 and 1997. A number of variables that may have influenced the success rate were examined. Findings indicated that the type of institution in which the Principal Investigator (PI) was employed and from which the proposal was submitted, the number of years since the PI had earned his or her Ph.D., and membership in the Law and Society Association at the time of the proposal was submitted were significant factors. It was found that, on average, proposals were successful 30 percent of the time. Furthermore, persistence was revealed to be a valuable strategy—proposals resubmitted for consideration after having been declined were more likely to be funded.